2014
DOI: 10.1542/peds.2013-0655
|View full text |Cite
|
Sign up to set email alerts
|

Stabbing Headache in an 8-Year-Old Girl: Primary or Drug Induced Headache?

Abstract: The occurrence of stabbing headaches in children requires a thorough diagnostic approach that excludes secondary headaches. The organic background should be taken into consideration when alarming symptoms occur, such as a purely 1-sided location, a change in the character of the headache, or possibly a link to physical activity. The current study describes the case of an 8-year-old girl who suffered short-lasting stabbing headache attacks. The headaches with increasing intensity and frequency started 1 month b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…Surprisingly, in 76.5% of patients in this review, pain occurred at night and on waking up. The exact time of pain onset was not recorded but it usually started about 90 minutes after Verapamil 3,10,15,16,21 8 -1 7 100.0 Gabapentin 14,15 4 --4 100.0 Methysergide 12,15 4 -1 3 100.0 Indomethacin 2,5,6,9,11,12 falling sleep; this nocturnal occurrence was reported in other studies. 25 In this review, we investigated family history and found that 9.8% of patients had a family member with cluster headache, 6,11,15,21 which is in line with a previous study that found a percentage of 17.5%.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Surprisingly, in 76.5% of patients in this review, pain occurred at night and on waking up. The exact time of pain onset was not recorded but it usually started about 90 minutes after Verapamil 3,10,15,16,21 8 -1 7 100.0 Gabapentin 14,15 4 --4 100.0 Methysergide 12,15 4 -1 3 100.0 Indomethacin 2,5,6,9,11,12 falling sleep; this nocturnal occurrence was reported in other studies. 25 In this review, we investigated family history and found that 9.8% of patients had a family member with cluster headache, 6,11,15,21 which is in line with a previous study that found a percentage of 17.5%.…”
Section: Discussionmentioning
confidence: 88%
“…During pain attacks, the most effective abortive agents in most patients are inhalation of 100% oxygenbetween 7L/min and 12L/min for 15 to 30 minutes through a face maskand subcutaneous and intranasal triptans. 3,[8][9][10][11][12][13][14] Verapamil, lithium, topiramate, gabapentin, indomethacin, and valproic acid/sodium valproate are the most used prophylactics. 2,3,5,6,[9][10][11][12]15,16 However, verapamil is the drug of choice in this age group and in adults.…”
mentioning
confidence: 99%
“…Diversos estudios muestran que la CPP con localización occipital/nucal ocurre entre el 39% y el 58% de los casos, en la región fronto-temporal entre el 39% y el 62% y tiene localización parietal en el 18% al 49% 3,15,16 . Usualmente los episodios ocurren de manera espontánea, aunque se han reportado algunos desencadenantes como cambios climáticos, luces brillantes, falta de sueño, estrés emocional y fármacos 3,15,17,18 . Las comorbilidades no son frecuentes en niños y los estudios de neuroimagen suelen ser normales 19 .…”
Section: Discussionunclassified
“…Durante as crises de dor, os agentes abortivos mais eficazes na maioria dos pacientes são a inalac ßão de oxigênio a 100%, entre 7L/min e 12L/min por 15 a 30 minutos atrav es de uma m ascara facial -e triptanos subcutâneos e intranasais. 3,[8][9][10][11][12][13][14] Verapamil, l ıtio, topiramato, gabapentina, indometacina e valproato são os profil aticos mais utilizados. 2,3,5,6,[9][10][11][12]15,16 No entanto, o verapamil e a droga de escolha nessa faixa et aria e adultos.…”
unclassified